Structural analysis of some Escherichia coli capsular antigens - Hackland, Peter Linton (Rhodes University, Faculty of Pharmacy, Pharmacy, 1992)
The work presented in this thesis forms part of a collaborative effort to determine the chemical structures of the surface antigens of bacteria which belong to the Enterobacteriaceae. These antigens are largely polysaccharides and occur as lipopolysaccharides and capsular polysaccharides which give rise to the somatic or 0 antigens and the capsular or K antigens, respectively. In recent years interest has mostly been focused on the extracellular polysaccharide antigens expressed by the genus Escherichia coli because of the effect they exert on normal immunological processes and their structural relatedness to the surface antigens of other more pathogenic bacteria. Therefore the molecular structures of the capsular polysaccharides (Kantigens)produced by E. coli 09:K35(AI04a) and 09:K38(A262a) have been determined by novel enzymic, chemical and spectroscopic procedures. These investigations show that the structures of these polysaccharides can be determined by a combination of chemical and spectroscopic procedures , or almost entirely by n.m.r. spectroscopy alone. The in vitro bacteriophage mediated depolymerisation of the native E. coli K35 polysaccharide demonstrates the value of this method for the isolation of oligosaccharides representing the repeating- unit and multiples thereof. Finally E. coli K37 and K38 capsular polysaccharides were used as model compounds for the evaluation of partial and selective reductive cleavage as methods of generating oligosaccharide for further structural analysis. The products of these reactions were analysed largely by a combination of mass spectrometric procedures.
Keywords: Antigens; Enterobacteriaceae; Escherichia